ANALISIS KINERJA GURU DALAM MENGELOLA PEMBELAJARAN DARING DI TK NEGERI PEMBINA SABAK AUH - Enda Puspitasari; Nofita Sari; Ines Permata Sari Tarigan; Sarah Putri Syafira (STKIP Pesisir Selatan, 2022)
Observations were made with the aim of obtaining information about teacher performance in managing online learning at TK Negeri Pembina Sabak Auh, Siak Regency, with the objectives of 1) describing teacher performance in planning online learning at TK Negeri Pembina Sabak Auh, Siak Regency, 2) Describing teacher performance in carry out online learning at the Pembina State Kindergarten of Sabak Auh, Siak Regency, 3) Describe the teacher's performance in evaluating online learning. The data collection method used is observation and documentation. The data analysis technique used is descriptive qualitative. The results of the researcher's observations show that the performance of teachers in managing online learning during the COVID-19 pandemic can plan online learning activity programs, carry out online learning activities, and evaluate online learning properly according to the standards set in online learning.